A novel hybrid coagulation-intermittent sand filter for the treatment of dairy wastewater. (1st October 2022) - Mohamed, A.Y.A.; Siggins, A.; Healy, M.G.; Fenton, O.; Ó hUallacháin, D.; Tuohy, P.
Abstract: An intermittent sand filter (ISF) is a simple and cost-effective treatment method that may be adopted on farms to treat dairy wastewater (DWW). However, the use of ISFs has been limited due to the large area required for treatment, and the risk of filter clogging and phosphorus (P) breakthrough, which decrease the operational lifetime. To overcome these limitations, this study uses a novel, pilot-scale coagulation-sedimentation process prior to loading ISFs with DWW. The performance and operational lifetime of this new hybrid coagulation-ISF system was compared to a conventional ISF system in a replicated outdoor pilot-scale experiment over a 43-wk study duration (covering an entire milking season on a farm in Ireland). The hybrid system was able to operate effectively at a higher hydraulic loading rate than a conventional ISF system. The effluent quality from the conventional ISF deteriorated over the timeframe of the study until clogging occurred, while the hybrid system continued to perform effectively without any evidence of clogging or P breakthrough. The hybrid system obtained removal efficiencies ≥99% for all measured water quality parameters (chemical oxygen demand, total suspended solids, total P, ammonium and turbidity), and complied with EU directives concerning urban wastewater treatment. Overall, the hybrid coagulation-ISF is a promising technology that requires a small area (75% reduction in footprint in comparison to a conventional ISF) and minimal operator input, and produces high effluent quality. Graphical abstract: Image 1 Highlights: Performance of novel hybrid coagulation-ISF was compared to conventional ISF. The coagulation-ISF system required only 25% of the conventional ISF size. The coagulation-ISF system did not experience any clogging or P breakthrough. The conventional ISF encountered both clogging and P breakthrough. The coagulation-ISF produced better effluent quality than conventional ISF.